Evaluating performance of container terminal operation using simulation - Mohd Nawawi, Mohd Kamal; Che Jamil, Fadhilah; Mohamad Hamzah, Firdaus (2015)
A container terminal is a facility where containers are transshipped from one mode of transport to another. Congestion problem leads to the decreasing of the customer’s level of satisfaction. This study presents the application of simulation technique with the main objective of this study is to develop the current model and evaluate the performance of the container terminal. The suitable performance measure used in this study to evaluate the container terminal model are the average waiting time in queue, average of process time at berth, number of vessels enter the berth and resource utilization. Simulation technique was found to be a suitable technique to conduct in this study. The results from the simulation model had proved to solve the problem occurred in the container terminal.